A community approach to language documentation in Africa - (:unkn) unknown (My University, 2024)
Although still not common, some recent language documentation projects in Africa have adopted the community-based approach (Good 2012; Bischoff & Jany 2018) which allows for the participation of community members at various stages of the documentation process. This approach is highly favored over the traditional method of linguistic inquiry that was based on the speech of one or a few individuals, i.e. the 'ancestral code' (Woodbury 2011). However, it appears that even within this current framework, the linguist reaps the greatest academic and financial benefits while community members end up with linguistic outputs that do not meet their current livelihood needs. I argue in this paper that instead of focusing on the documentation of African languages while neglecting current survival needs of community members, and thereby legitimizing and accompanying language death, linguists and funding agencies should conceive linguistic projects as community development projects. If linguistic projects assist in community development and maintenance, languages and cultures are more likely to be preserved, making linguistic work meaningful and useful to African communities.
Keywords: African Research